A Low-Power LTPO Scan Driver Circuit Using DC Power Supplied Buffer - SangWoon Lee; JungSuk Oh; HyeongMin Kim; YiKyoung You; Nack-Hyeon Keum; HeeJu Moon; SangHun Kim; KeeChan Park; Hwarim Im (IEEE Journal of the Electron Devices Society)
This paper proposes a novel low-temperature polycrystalline silicon and oxide (LTPO) scan driver circuit integrating p-channel low-temperature polycrystalline silicon (LTPS) thin-film transistors (TFTs) and n-channel metal-oxide (MOx) TFTs. The proposed circuit employs a complementary metal-oxide-semiconductor inverter as an output buffer, allowing low-level voltage to be delivered from a DC power supply to the output node without relying on clock-supplied bootstrapping, which is typically required in most scan driver circuits to drive the output buffer. This design significantly lowers dynamic power consumption by up to 74% by reducing the power consumption due to charging/discharging the parasitic capacitance of the buffer TFT by the clock signals compared with the conventional LTPO scan driver circuits utilizing the clock-supplied bootstrapping method. Additionally, the proposed circuit reduces the positive bias applied to MOx TFTs to alleviate stress conditions effectively. Therefore, the proposed circuit can improve long-term reliability by mitigating the threshold voltage shifts of MOx TFTs.